2019
DOI: 10.18805/lr-4074
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of chemical insecticides against major sucking insectpests on grain legumes in India- A review

Abstract: Grain legumes are the important source of dietary protein in tropical regions and insect pests are the major biotic constraints in the production of the grain legumes throughout the country. About 150 species of insects are known to attack pulse crops in India. Among the insect pests, the sucking pests like aphid, Aphis craccivora Koch; jassid, Empoasca kerri Pruthi; whitefly, Bemisia tabaci Gennadius, thrips,Thrips palmi Karny and flower thrips, Megalurothrips usitatus Bagnall are know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…Pigeonpea is one of the major drought resistant pulse or grain legume cultivated in semiarid tropical and subtropical regions of the world mainly for its protein enriched seeds (both green and dry grains) and also as vegetable source (Shanower et al, 1999;Nene et al, 1990;Seetharamu et al, 2020). Its mature green pods are used as a vegetable and de-hulled seed are used along with rice and bread.…”
Section: Introductionmentioning
confidence: 99%
“…Pigeonpea is one of the major drought resistant pulse or grain legume cultivated in semiarid tropical and subtropical regions of the world mainly for its protein enriched seeds (both green and dry grains) and also as vegetable source (Shanower et al, 1999;Nene et al, 1990;Seetharamu et al, 2020). Its mature green pods are used as a vegetable and de-hulled seed are used along with rice and bread.…”
Section: Introductionmentioning
confidence: 99%
“…Coleopterous weevils and Lepidopterous stalk borers are the most devastating insects in both fields and stores (Hiruy and Getu, 2018b). Many insects are pathogenic, they also transmit diseases and physical destruction (Seetharamu et al, 2020).…”
Section: Causes Of Postharvest Lossesmentioning
confidence: 99%
“…Residual chemicals insecticides in grains were reported to cause health problems (Said and Pashte, 2015). Their indiscriminate use can lead to resistance and revival in insects and leach and contaminate the environment (Seetharamu et al, 2020). Teló et al (2017) reported the presence of pre-harvest insecticide residues in rice husk.…”
Section: Synthetic Chemicalsmentioning
confidence: 99%
“…Megalurothrips usitatus (Bagnall), belonging to the suborder Thysanoptera, is a pest that is a major threat to legumes (Du et al, 2019 ; Wang et al, 2019 ; Seetharamu et al, 2020 ). The flowering period of crops is particularly vulnerable to damage by M. usitatus , which causes huge economic losses to crops due to the deformity of and scars on petals and fruits (Zhang et al, 2007 ; Tang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%